The Turkish experience with therapeutic plasma exchange: A national survey. (June 2019) - Korkmaz, Serdal; Solmaz Medeni, Serife; Demirkan, Fatih; Kalayoglu Besisik, Sevgi; Altay Dadin, Senem; Akgun Cagliyan, Gulsum; Kabukcu Hacioglu, Sibel; Sari, Ismail; Goren Sahin, Deniz; Arat, Mutlu; Dagdas, Simten; Ozet, Gulsum; et al.
Abstract: Therapeutic plasma exchange (TPE) is used to treat more than 60 diseases worldwide and has drawn growing interest. Little is known about the current situation of TPE activity in Turkey, so we developed a survey to obtain information about this timely topic. We collected data on TPE from 28 apheresis units throughout Turkey. We performed a total of 24, 912 TPE procedures with 3203 patients over the past decade. Twenty years ago, the majority of procedures were performed for neurological and hematological disorders, and today, most TPE procedures are done for the same reasons. The only historical change has been an increase in TPE procedures in renal conditions. Currently, renal conditions were more frequently an indication for TPE than rheumatic conditions. Fresh frozen plasma was the most frequently used replacement fluid, followed by 5% albumin, used in 57.9% and 34.6% of procedures, respectively. The most frequently used anticoagulants in TPE were ACD-A and heparin/ACD-A, used with 1671 (52.2%) and 1164 (36.4%) patients, respectively. The frequency of adverse events (AEs) was 12.6%. The most common AEs were hypocalcemia-related symptoms, hypotension, and urticaria. We encountered no severe AEs that led to severe morbidity and mortality. Overall, more than two thirds of the patients showed improvement in the underlying disease. Here, we report on a nationwide survey on TPE activity in Turkey. We conclude that there has been a great increase in apheresis science, and the number of TPE procedures conducted in Turkey has increased steadily over time. Finally, we would like to point out that our past experiences and published international guidelines were the most important tools in gaining expertise regarding TPE.